Chronic Myelomonocytic Leukemia Associated With TAFRO Syndrome-Like Symptoms - Issam Drici-Tani; Lucile Grange; Martin Killian; Jean-Baptiste Gaultier; Michel Péoc'h; Manon Sapet; Ludovic Fouillet; Emmanuelle Tavernier-Tardy; Émilie Chalayer (Annals of Internal Medicine: Clinical Cases)
Thrombocytopenia, anasarca, fever, reticulin fibrosis, renal dysfunction, and organomegaly (TAFRO) syndrome is a recent disease concept whose physiopathology remains largely unknown. Association of TAFRO syndrome features with immune-mediated or hematologic disorders have been reported but have not been reported with chronic myelomonocytic leukemia. Chronic myelomonocytic leukemia (CMML) is a myeloproliferative/myelodysplastic syndrome that is frequently associated with autoimmune or autoinflammatory features. Herein, we report 2 cases of CMML-associated TAFRO syndrome-like symptoms. The first one was fatal, and the second one was successfully treated with siltuximab. These reports question the Masaki criteria for TAFRO syndrome diagnosis, which require excluding an autoimmune, neoplastic, or infectious condition beforehand.